Climate-Driven Range Shifts Are Rapid Yet Variable Among Recreationally Important Coastal-Pelagic Fishes - Champion, Curtis; Brodie, Stephanie; Coleman, Melinda A. (Frontiers in Marine Science, 2021)
Shifts in species distributions are occurring globally in response to climate change, but robust comparisons of redistribution rates among species are often prevented by methodological inconsistences, challenging the identification of species that are most rapidly undergoing range shifts. In particular, comparable assessments of redistributions among harvested species are essential for identifying climate-driven changes in fishing opportunities and prioritising the development of management strategies. Here we utilise consistent datasets and decision rules to comparably analyse rates of climate-driven range shifts over 21 years for four recreationally important coastal-pelagic fishes (Australian bonito, Australian spotted mackerel, narrow-barred Spanish mackerel and common dolphinfish) from the eastern Australian ocean warming hotspot. Latitudinal values corresponding to the poleward edge of species’ core oceanographic habitats were extracted from species distribution models. Rates of poleward shifts in core oceanographic habitats ranged between 104.3 (i.e. common dolphinfish) and 289.1 (i.e. narrow-barred Spanish mackerel) km per decade for all species over the study period. However, rates of redistribution varied by approximately 180 km per decade among species, demonstrating that subtle differences in species’ environmental responses can manifest in highly variable rates of climate-driven range shifts. These findings highlight the capacity for coastal-pelagic species to undergo rapid, yet variable, poleward range shifts, which have implications for ecosystem structure and the changing availability of key resources to fisheries.